Entre ditos e não ditos: a marcação social de diferenças de gênero e sexualidade por intermédio das práticas escolares da Educação Física - Prado, Vagner Matias do [UNESP] (2014)
Physical education is part and parcel of the discursive systems that construct representations of standardized behaviors in our society. Sporting a different physique than that set by the commonly accepted standards of health and beauty, not adhering to socially appropriate gender behaviors, or running afoul of the system of cultural intelligibility that demands a causal and ordered relationship between sex, gender and sexuality are markers that indicate differences in physical education classes at school. By relying on the theoretical framework of poststructuralist studies and queer theory, we aim to understand how the discourses used by the discipline produce standards for gender and sexuality, using heterosexuality as a normative baseline. We researched subjects who questioned the standards of heterosexual normality as represented in academic spaces and how they built the defenses that allowed them to transit in these spaces. The survey was developed with young gay adults in the city of Presidente Prudente - SP. Through the use of socioeconomic questionnaires and the development of six (6) semi-structured interviews, we analyzed reports of the experiences of the subjects, who self-represent as homosexuals, from their recollections of physical education classes throughout basic education. The results obtained indicate that Physical Education is managed by the regulatory gender mechanisms in which heterosexuality is taken as a standard of normality. Subjects who did not demonstrate hegemonic masculinity, as grounded in the notion of virility and female subjugation, are constant targets of labeling that aim to materialize their lack of adequacies in the school setting and, more specifically, within the context of physical education classes.